2008
DOI: 10.1300/j027v27n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Workers' Compensation and Medical Care for Injured Personal Assistance Services Workers

Abstract: The lack of a traditional employment infrastructure has important implications for vulnerable workers' health and the sustainability of consumer-directed PAS programs. We provide recommendations for improving workers' access to workers' compensation and injury-related medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Both types of rates were reported to provide a range of likely differences in injury rates between temporary and permanent workers. In addition, WC data has a number of inherent limitations, including under‐reporting and differences between states in terms of reporting and compensability requirements. Finally, about 60% of the companies insured by OHBWC are small employers with a payroll of less than $100 000.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of rates were reported to provide a range of likely differences in injury rates between temporary and permanent workers. In addition, WC data has a number of inherent limitations, including under‐reporting and differences between states in terms of reporting and compensability requirements. Finally, about 60% of the companies insured by OHBWC are small employers with a payroll of less than $100 000.…”
Section: Discussionmentioning
confidence: 99%
“…If effective, the programs could be expanded or replicated in other regions. In a qualitative study of injured PAS providers [26] , relative and non-relative providers described home environments in which ergonomic lifting or transfers was difficult to impossible, or lift equipment was not utilized because of recipient fears, provider difficulty, or lack of space in which to maneuver the equipment. What may be even more relevant than research or intervention regarding the physical home care work environment, however, is increased resources for assistance for obtaining and correctly utilizing lift equipment or other safety devices, or modifying the recipient's home so that PAS may be provided in a more ergonomic environment.…”
Section: Directions For Future Research: Healthy Physical and Temporamentioning
confidence: 99%
“…WC data also have a number of limitations as surveillance sources, including under‐reporting of OII and state differences in reporting and compensability. Similar to SOII and OSHA recordable data, a number of studies have noted that WC data suffer from the under‐reporting of OII, especially illnesses, with up to an estimated 50% or more of the compensable injuries going unreported [Biddle et al, ; Rosenman et al, ; Azaroff et al, , ; Fan et al, ; Scherzer and Wolfe, ; Lipscomb et al, ]. For example, a large review of WC claims in Michigan [Biddle et al, ] found especially elevated rates of under‐reporting in certain higher risk industries such as manufacturing and in cases involving “chronic conditions with long latency periods between exposure and development of disease.” Azaroff et al [] reported several barriers to WC reporting, including “lack of familiarity with WC, uncertainty about work‐relatedness, and reliance on patients to identify work‐relatedness of their conditions.” Non‐reporting of WC claims by workers to employers can also be due to a fear of employer retaliation that similarly impacts the reporting of OSHA recordables.…”
Section: Introductionmentioning
confidence: 99%